Material selection of intraoral stents for head and neck cancer patients undergoing radiation therapy: A Multi-criteria, Multi-physics design approach. (January 2023) - Kazemian, Negin; Fowler, James D.; Muhammad Khalid, Faizan; Milligan, Kirsty; Alousi, Sahar; Sabry, Sebastian; Pada, Hilary; Araujo, Cynthia; Jirasek, Andrew; Milani, Abbas S.; Pakpour, Sepideh
Graphical abstract: Highlights: A multi-physics, multicriteria design approach developed for material selection of intraoral stents for head and neck cancer (HNC) radiation therapy. Candidate materials assessed using Raman spectroscopy and mechanical testing pre- and post-treatments to saliva and radiation exposure. Leaching for toxicity assessed using NMR spectroscopy. Overall, ethylene vinyl acetate (EVA) was deemed as a non-toxic appropriate candidate to reduce/avoid significant side effects for HNC patients. Abstract: Radiation therapy (RT) plays a key role in curative-intent treatments for head and neck cancer (HNC). Despite the advancements in RT, high doses of radiation can disrupt the oral cavity homeostasis and result in undesired reactions. Thus, intraoral stents (IOSs) are utilized for patients during RT to prevent unnecessary irradiation to surrounding tissues. However, no studies have compared commonly used IOS materials and their potential toxicity. Therefore, the objective of this study is to perform a detailed assessment of ten IOS materials in order to select the top-ranked material for HNC patients undergoing RT. Thus, beam attenuation measurements, and Raman spectroscopy and mechanical testing were conducted pre- and post-artificial saliva, RT, and artificial saliva and RT exposure. Finally, through a multi-criteria decision making (MCDM) analysis using Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS), our study demonstrated that Ethylene Vinyl Acetate (EVA) was the top-ranked material. The saliva samples were also tested via nuclear magnetic resonance (NMR) spectroscopy, which showed no leaching of irradiated materials. Taken together, these data suggest that EVA is an appropriate IOS material that can be utilized during RT to reduce significant morbidity for HNC patients and improve their quality of life.